Ventilatory response and delirium risk in hospitalised patients with acute hypoxia due to COVID-19 - Nikolai Ravn Aarskog; Hanna Othilie Lindvig Bjørsrud; Aleksander Rygh Holten; Leiv Otto Watne; Bjørn Erik Neerland; Morten Rostrup (Scientific Reports)
Abstract Mountaineers with a high ventilatory response to hypoxia experience greater cognitive impairment at high altitude, possibly because hyperventilation causes hypocapnia, cerebral vasoconstriction and ultimately cerebral ischaemia. We hypothesised that a high ventilatory response, and consequently a lower arterial partial pressure of carbon dioxide (PaCO2), could increase the risk of delirium in hospitalised patients with acute hypoxia. To test our hypothesis, we conducted a cohort study in which PaCO2 and arterial oxygen saturation were measured upon hospital admission in 126 patients with COVID-19. After adjusting for oxygen saturation, we found that a lower PaCO2 was associated with a higher risk of delirium during hospital admission (risk ratio 1.67 [95% confidence interval 1.09–2.54] per 1 kilopascal reduction, P = 0.017). The association remained statistically significant after adjusting for other well-established risk factors for delirium. This finding supports our hypothesis that a high hypoxic ventilatory response increases the risk of delirium in patients with acute hypoxia.